Communicative competence formation of future engineers and teachers in the pedagogical activity process - Bobrikova, Y. (Problems of Engineer-Pedagogical Education, 2018)
The article discusses issues related to the communicative competence formation of future engineers and teachers in the pedagogical activity process. The theoretical development of communicative competence of engineers and teachers were described, criteria and levels of professional communicative competence of future engineersteachers were made, and the urgency of the problem of professional competence formation of engineer-teacher was proved with constant transformationsocial experience, the reconstruction of education activity, the emergence of various typesauthor's pedagogical systems, the change in the level of social inquiries for the specialist. The essence and structure of professional communicative competence of future engineersteachers, especially the communication indicator in the training of engineers-teachers, organizational and pedagogical conditions promoting formation of professional and communicative competence of future engineers-teachers, the functions and some elements of professional activity of engineer-teacher were discovered, what are the main aspects of professional competence formation of the individual in a higher education learning process.